The role of the spleen in mediating pathology in Plasmodium Yoelii (P.yoelii) infection - Huang, Ximei (2016)
Differences in the ability of the spleen to deal with the infected red blood cells (iRBCs) are linked to differences in virulence. Using virulent and avirulent Plasmodium yoelii strains, we investigated how parasite virulence modulates overall spleen function. Following parasite invasion, a difference in parasite virulence and the corresponding disease outcome was observed to associate with different spleen morphology, immune response and iRBC rigidity, all of which contributing to enhanced parasite clearance. The iRBC rigidity as modulated by the spleen was demonstrated to regulate disease outcome. Moreover, the early activation of pro-inflammatory responses in the spleen appears to help to control the parasite development, confirming that early spleen responses are a key factor in directing the clinical outcome of an infection. This work highlights the biological responses to control malaria disease development, and also provides a potential tool for fast and easy diagnosis and prognosis of malaria patients.